2021
DOI: 10.1177/00368504211033677
|View full text |Cite
|
Sign up to set email alerts
|

Crossbreed impact of double-diffusivity convection on peristaltic pumping of magneto Sisko nanofluids in non-uniform inclined channel: A bio-nanoengineering model

Abstract: The consequences of double-diffusivity convection on the peristaltic transport of Sisko nanofluids in the non-uniform inclined channel and induced magnetic field are discussed in this article. The mathematical modeling of Sisko nanofluids with induced magnetic field and double-diffusivity convection is given. To simplify PDEs that are highly nonlinear in nature, the low but finite Reynolds number, and long wavelength estimation are used. The Numerical solution is calculated for the non-linear PDEs. The exact s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The conservation of energy for heat transfer is given by the constitutive equation as 7 , 38 , 49 : where .…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The conservation of energy for heat transfer is given by the constitutive equation as 7 , 38 , 49 : where .…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The nanoparticles volume fraction equation can be written as the mathematical formula as follows 7 , 38 : …”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they observed that non-Newtonian fluids caused by stretching sheets provide a significant engineering and technological problem because of their widespread engineering and technological applications in a variety of industrial and engineering processes [14][15][16][17][18][19]. In references [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], you can find some additional interesting contributions on Newtonian and non-Newtonian nanofluid flow and its applications in manufacturing. The fundamental purpose of this research is to look at the heat transfer properties of an Eyring-Powell fluid flow caused by a stretching sheet immersed in a porous media and influenced by thermal radiation.…”
Section: List Of Symbols Umentioning
confidence: 99%